How to Assess the Benefits of Nonperforming Loan Disposal in Sub-Saharan Africa Using a Simple Analytical Framework - Bunda, Irina (IMF How To Notes; How-To Note ;, 2021)
The coronavirus (COVID-19) crisis, which has hit financial systems across Africa, is likely to deteriorate banks' balance sheets. The largest threat to banks pertains to their loan portfolios, since many borrowers have faced a sharp collapse in their income, and therefore have difficulty repaying their obligations as they come due. This could lead to a sharp increase in nonperforming loans (NPLs) in the short to medium term.